KINERJA BADAN PERMUSYAWARATAN DESA (BPD) DALAM MENJALANKAN FUNGSINYA (Studi Kasus di Desa Tanjung Laong Kecamatan Muara Pahu Kabupaten Kutai Barat ) - Herlisa, Maskan AF, dan Salasiah (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2022)
This study aims to determine how the performance of BPD in carrying out itsfunctions. This type of research uses qualitative research with descriptive type, the numberof informants in this study is 7 people who are determined by data collection techniquesusing interview and documentation methods. The focus of this research is to protect,legislate, supervise, and accommodate people's aspirations. The results showed that theperformance of BPD in the act of nurturing socially had been carried out well, but it wasstill not optimal. Performance in legislation itself has several obstacles, namely the lackand lack of knowledge from the village government and the BPD who conduct jointdeliberation in forming a decision and formulating a village regulation itself and the lackof cooperation with each other. Performance in monitoring actions is optimal enoughwhere the BPD often makes social visits to the community to listen to aspirations orcomplaints that the community wants to convey to the village government. Performance incommunity aspirations, the BPD has sought all forms of community aspirations to beheard by the village government. Overall, the performance of the BPD in this case hasbeen very good in desensitizing and channeling the aspirations of the community so thatthey are heard and considered to be resolved properly.